PENGGUNAAN METODE GRANGER UNTUK UJIKAUSALITAS - Purnomo, Didit (Jurnal Ekonomi Pembangunan: Kajian Masalah Ekonomi dan Pembangunan, 2001)
The relationship between variables is close to regression analysis. This article tries to give a few contributions about one of model which uses regression analysis assistance, i.e. Granger method. The method explains reciprocal or causality relationship of two variables, whether one variable explains another variable or vice versa.